2020
DOI: 10.1016/j.artd.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anesthesia Using Chloroprocaine is Safe, Effective, and Facilitates Earlier Discharge in Selected Fast-track Total Hip Arthroplasty

Abstract: Background: Spinal anesthetic choice plays an underappreciated role in total hip arthroplasty (THA). Chloroprocaine, a short-acting local anesthetic, has been limited to short-duration ambulatory procedures and has not been studied in THA. We compare perioperative outcomes of patients undergoing fasttrack THA using chloroprocaine spinal anesthesia with those who have surgery with a longer-acting agent (bupivacaine). Methods: A total of 143 THAs performed under spinal anesthesia by 3 arthroplasty surgeons betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…An alternative to lower doses of bupivacaine is to choose a different agent altogether. Recent research has shown promising results for shorter acting agents such as chloroprocaine, especially in select patients that can have their surgeries performed quickly [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to lower doses of bupivacaine is to choose a different agent altogether. Recent research has shown promising results for shorter acting agents such as chloroprocaine, especially in select patients that can have their surgeries performed quickly [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in the ambulatory setting for knee arthroscopy and foot procedures and less commonly in TJA. In a retrospective study of fast-track inpatient THA, patients who received 2-chloroprocaine (60 mg) SA had shorter LOS, shorter operative time, shorter PACU stay, less hypotension, less intraoperative blood loss, and were more likely to be discharged home compared to those who received bupivacaine (8–15 mg) [22]. In a meta-analysis comparing 2-chloroprocaine to “low-dose” bupivacaine SA (defined as <10 mg) in ambulatory procedures, use of 2-chloroprocaine resulted in faster return of motor and sensory function, shorter time to ambulation, and faster time to ambulation with no difference in onset time [23].…”
Section: Spinal Anesthesia For Ambulatory Total Joint Arthroplastymentioning
confidence: 99%
“…Indeed, some of the current recommendations are not applicable to ambulatory hip replacement. Pain management for ambulatory hip replacement may feature one or more major practice modifications, such as use of short‐acting spinal anaesthetics, avoidance of intrathecal long‐acting opioids and avoidance of nerve blocks that compromise motor strength and impede ambulation [8]. Future research is obviously needed to determine whether or not a trade‐off between long‐acting intrathecal opioids and motor‐sparing blocks will improve patient outcomes.…”
Section: What Continues To Be Missing?mentioning
confidence: 99%